(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To compare outcomes in patients with ischemic stroke aged 18 years and older who received endovascular intervention within 6-16 hours versus within 16 hours based on perfusion imaging and core infarction discordance. Subject and methods: Retrospective analysis was conducted on data collected (prospectively) in patients treated with endovascular intervention in the anterior circulation, after 6 hours from onset. A modified Rankin score (mRS) of 0-2 is considered good functional outcome at 90 days. Patients were selected based on clinical and imaging discordance based on the criteria of the DEFUSE 3 study in both groups except for time criteria. Results: Among 165 patients with large cerebral embolic stroke in the study, 79 patients (47.9%) received endovascular intervention within a window after 16 hours from the time of onset; 86 patients (52.1%) received intervention within a 6-16 hour window. Patients in the 6-16 hour window group had a shorter time from onset to femoral artery puncture than those in the 16 hour window group (median 12.2 hours vs 20.5 hours, p < 0.001). There was no statistically significant difference between the two groups in terms of NIHSS score (median 14.5 vs 15.0, p = 0.46). Perfusion imaging characteristics (infarct core: median 9 ml vs 9 ml, p = 0.67; penumbra volume: median 112 ml vs 103 ml, p = 0.61; discordance ratio: median 7.1 vs 7.24, p = 0.88) and time from perfusion imaging to femoral artery puncture (median position 73 minutes vs 81 minutes, p = 0.2). There was no significant difference between the two groups in functional independence (48.8% vs 44.3%, p = 0.56), 90-day mortality (9.3% vs 13.9%, p = 0.35), successful cerebral revascularization rate (91.9% vs 82.3%, p = 0.065), symptomatic cerebral hemorrhage (2.3% vs 3, 8%, p = 0.67). Conclusion: In this study, regardless of the time window, patients selected for endovascular treatment based on perfusion imaging and core infarction discordance had similar outcomes.